Spatial-economic characterization of resilient urban destinations - Lew, Shian Loong (2012)
Ironically globalization has made a destination’s location important but its distance negligible. How do destinations maintain their resilience in such a context? There is a need for a spatial-economic characterization of resilient urban destinations. In a weightless world, demand intangibility must match supply tangibility.Chapter 2 suggests that resilience requires fitness. In the context of tourism this condition of information symmetry is initialized when space acts as an interface, encouraging visitor-destination interactions, and therefore enhances place-making. Computer simulations demonstrated how the right rules led to information symmetry, scaling up from visitor micromotives to destination-level macrostructures. As an axiom, optimal destination resilience coincides with the highest irreducible complexity. Chapter 3 outlines the rule or heuristic to follow to estimate irreducibility at destinations. In a borderless world, such a condition is met where transitions and convergences coincide in the destination’s growth path. A visual phenomenology is used to categorize transitions; while an index measures convergences. In an interlinked world, destinations need to be locally-authentic while being globally-popular. Chapter 4 suggests that it is sufficient that a resilient destination be poised for change. Venice was chosen as an archetypical case for urban destination accessibility. Two sample administrative regions were chosen to reflect its local-global accessibility. Cannaregio was chosen for its localized authenticity and San Marco for its global popularity. The findings in Chapter 4 demonstrated how, visitor, place-related information, derived from geo-tagged images can be complemented with topographical, geographical information derived from satellite images to serve as reliable proxies for authenticity popularity levels at urban destinations; allowing us to make inferences concerning an urban destination’s resilience. Each chapter offered a different angle to resilience that contributed to the robustness of the characterization. Specific insights were gained with respect to destination design and planning, destination development and positioning; and finally destination resilience. Faced with the challenge of weightlessness, the design and planning of a destination should be guided by visitorscentric information. Visitors act as sensors within the destination space, like pixels on a screen, they highlight the meaningful places embedded within the public space. Faced with the challenge of borderlessness, destination development and positioning should be achieved through a co-evolutionary approach. This adaptive management of destinations recognizes that coordination between visitors and destinations is needed to achieve irreducible complexity. Faced with the challenge of interlinkages, the ruleof-thumb for destination resilience is time-space accessibility, boiling down resilience to a right balance between place and space. The popularity mandate requires a prolonged experience of time at destinations, in spite of the limited destination space. This can be achieved through the creation of microcosms, essentially “one space many places”. The authenticity mandate requires shortening the experience of time at destinations in spite of the extensive destination space. This can be achieved through the creation of heterotopias, essentially “one place many spaces”. The resilient destination, having aspects of popularity and authenticity, is a synthesis of the two, allowing heterotopias and microcosms to co-exists in a third place, effectively fusing work and play at destinations.